Dynamics of the radio landscape in India - Ananya, Roy (2009)
Radio has existed in India for more than 75 years. Yet, erroneous policies, tight regulation till of late, complete State control, an undefined financial model and lack of vision has kept this easily diffusible technology from becoming an effective medium for communication in the country till now.